The Effectiveness of Entonox When Comparing to Pethidine for Labor Pain:: A Systematic Review (Proceedings of the International Conference on Public Health, 2020)
Labour pain is considered as one of the most severe and intolerable pain in the world. Therefore several type of analgesia are used to relieve the labour pain. In 1934 Minnitt has intended a self-administration machine to inhale nitrous oxide. In England and both Asian and European countries have been using it for 60 years. Since 1950, pethidine is used in the England independently by the midwife to relieve the labour pain although it has a few side effects. This study was conducted to detect the best analgesia to manage labour pain among pethidine and Entonox. The aim of this study was to compare Entonox and pethidine to identify the most effective method to manage the labour pain. Systematic review of six primary quantitative studies, which were done according to the randomized control trial was conducted. Inclusion criteria were term, normal cephalic fetus in active phase of labour mothers who were having pethidine or nitrous oxide (Entonox) as labour analgesia. This study consisted of 596 participants worldwide. Findings reveal that Entonox helps to reduce the duration of labour, severity of labour pain and higher satisfaction than pethidine. In Conclusion, Entonox has more beneficial effects to relieve labour pain in the first stage of labour than pethidine.
Keywords: Labour pain; best analgesia; Entonox; pethidine